Problem Based Learning Models Helped by Student Worksheets Improve Higher Order Thinking Skills - Sujana, I Wayan (Universitas Pendidikan Ganesha, 2023)
Using interesting learning media is rarely done, causing students difficulties in learning. In addition, teachers have difficulty creating learning processes using various learning models, so students feel bored learning. This study aimed to analyze the LKPD Assisted Problem Based Learning Model in improving higher-order thinking skills in Grade V elementary school students. This type of research is quantitative research. This research is categorized as quasi-experimental research. The research design used was the one-group pretest-posttest design. The population in this study were all fifth-grade elementary school students consisting of 2 classes. The sampling technique is purposive sampling. In this study, the data collection technique used was a test. The instrument used to measure higher-order thinking skills is a multiple-choice objective test. The data analysis technique used is parametric statistics, namely the t-test. The analysis results show differences in the level of critical thinking skills of fifth-grade students before using the LKPD-assisted Problem-Based Learning model and the fifth-grade students' critical thinking skills after using the LKPD-assisted Problem-Based Learning model. It was concluded that the Problem-Based Learning model assisted by LKPD could improve the critical thinking skills of fifth-grade students.